Effect of Loan Collection Procedures and Loan Default in Microfinance Institutions in Kirinyaga County (Global Journal of Management and Business Research, 2016)
This study examined the performance of Microfinance Institutions (MFIs) in Kirinyaga County and particularly the women groups affiliated to the Institutions because they are registered as social welfare groups,(save for deposit taking MFI'S) and therefore they are not regarded as financial institutions and hence not registered at all and are also not under the control of Central Bank of Kenya, or the Micro finance regulatory body The Research targeted 300 employees of MFIs under study. The findings indicated that the operations of MFIs have grown remarkably due to expansion in the informal sector activities coupled with bank's reluctance to fund the evolving small and medium enterprises. On the other hand, financial services provided by MFIs have not been given any publicity or indicated among financial institutions in the official financial statistics.
Keywords: kenya women finance trust; microfinance institutions; united nations capital development fund